Exporting and the business-to-business market : Alibaba.com - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
This case study examines the Chinese business-to-business website Alibaba.com and how it came to hold a 69% market share in the Chinese business-to-business e-commerce market. The company was established after its founder, Jeffrey Ma, noticed a gap in the market for Chinese business to export their goods and services to global importers.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Exporting and the Business-to-Business Market: Alibaba.com. In International marketing (pp. 407-408). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Industrial marketing -- Case studies; Export marketing -- Case studies